Sistemas emulsionados para análise de amostras com alto teor lipídico por espectrometria de absorção atômica - Ieggli, Carine Viana Silva (2010)
The attention to the knowledge of nutritional and toxicological profiles of foodstuffs is increasing. Therefore, methods that allow for the determination of components desirable or necessary, as essential elements, and of undesirable as heavy metals are of great importance. Atomic Absorption Spectrometry (AAS) is a robust and well established technique for the determination of several elements in the most varied types of samples. Spectrometric analyses are usually made with sample solutions obtained by decomposition processes or sample digestion. However, such procedures result in additional steps that can cause inconveniences such as contamination and losses during manipulation. Emulsified systems have been used in the preparation of samples with high fat content. Emulsifing makes the sample decomposition not necessary, allows reducing the final content of organic matter, and stabilizes the present oily content. In this work, emulsified systems were developed to measure several metals by AAS in samples such as chicken eggs, chocolates, rice oil, canola oil, sunflower oil, corn oil, soy oil, olive oil, margarine light, margarine and butter. The tensoactives used in this work were Triton X100, Triton 114 and Tween 80. Additional oily components, the octila estearato and the corn oil, were used to get better in the stability of the chocolate and egg emulsions. All of the emulsions were prepared using a specific sequence to guarantee the stability and a general procedure of emulsion preparation can be established: to weigh the surfactant, oily sample or additional oily component, when it is the case, and to put in beakers of 80 mL. Adding heated water under continuous agitation to happen the sample emulsification, after following adding water until to reach the final volume. Magnetic agitation should be maintained during the cooling. In the samples of emulsified eggs were determined Selenium (Se) for Graphite Furnace Atomic Absorption Spectrometry (GFAAS) and sodium, potassium, calcium, magnesium, zinc and iron for Flame Atomic Absorption Spectrometry (FAAS). The methods validations were accomplished with the Certified Material of Reference (CRM) Whole Egg Powder (RM 8415). The Se recovery was 95,2% of the certified value and for another metals the recoveries of the certified values varied from 97,5% for magnesium and 102,2% for sodium. The methods showed appropriate sensibility, precision and accuracy. Sodium, potassium, calcium, magnesium, zinc and iron were determined in chocolate samples emulsified by F AAS and micro-emulsions were applied for the determination of aluminum, copper and manganese by GF AAS. The validation of the method was against SRM Baking Chocolate (SRM 2384) and the recoveries of the certified values varied from 88,6% for potassium to 108% for manganses. In the emulsified samples of vegetable oils, margarine and butter were determined As, Cd, Cr, Cu, Mn, Ni and Pb by GF AAS and Na, K, Ca, Mg, Zn and Fe for FAAS. And each in case the best measurement conditions were selected and the operational parameters were fit. The results for accuracy with inorganic recovery assays varied among 90% (Na) to 112% (Fe) for the FAAS measurements and among 83% (Cd) to 121% (Pb) for the GFAAS measurements.